The Effect of Plant Population on Sunflower [Helianthus annus L.] seed yield in Southwestern Nigeria - OGUNREMI, E. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Field experiments were conducted at two locations during the early and late seasons of 1966 to 1968 to investigate effects of plant population on seed yields of sunflower, variety Russian Giant. Plant population treatments significantly influenced seed yields and yield components. Mean yields differed significantly between early and late seasons and highest yields of 2,822kg/ha and 1,238kg/ha were obtained at 18,000 plants/ha indicated as the optimum population. Significant population x location and location x season interactions were observed. High humidity in the rainforest zone resulted in severed head rot and low yields. It is suggested that sunflower varieties might differ in seed production efficiency.